Trap-Door Incision for Penetrating Thoracic Trauma: An Obsolete Approach? - Ana Fabregues Olea; Leire Zarain Obrador; Dolores Perez-Diaz; Fernando Turégano Fuentes (Case Reports in Surgery)
Penetrating injuries to the subclavian vessels are uncommon and very severe lesions. They are difficult to expose and carry a high mortality. “Trap-door” incisions have lately been dismissed as too mutilating for the occasional victim of a penetrating thoracic trauma with massive bleeding difficult that is to expose. We present a case of severe bleeding from a stab wound in the left subclavicular area in a heavy-built patient where a “trap-door” incision proved inevitable to expose and repair the injury, and most probably saved his life.